(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Guerrilla marketing is an unconventional marketing tool which has developed importance in the modern market. This concept has enabled the companies to stand out from the crowd by using cost-effective ways. Additionally, people are on social networks, and the relationships are becoming more and more integrated into everyday life. Social media tactics can be targeted, are inexpensive, and very personalized, and coordinated with offline street team work. As a result, businesses have increased the rate of targeting consumers who are on social media networks by using guerrilla marketing. Even in the season of elections, many political parties are using this concept to reach every section of the society. This paper discusses how businesses and political parties have increased the rate of targeting their consumers and voters respectively with the help of guerilla marketing and allows it to affect their decisions. Moreover, the paper explores the challenges and opportunities which businesses and political parties have with guerrilla marketing. The paper also examines the present trends of guerrilla marketing in India and describes the reason why companies and political parties are adopting it and concludes that guerrilla marketing is something that will continuously grow in both practice and demand.